2022
DOI: 10.3389/fimmu.2022.1032411
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune responses to CoronaVac up to one year after vaccination

Abstract: Coronavac is a widely used SARS-CoV-2 inactivated vaccine, but its long-term immune response assessment is still lacking. We evaluated SARS-CoV-2-specific immune responses, including T cell activation markers, antigen-specific cytokine production and antibody response following vaccination in 53 adult and elderly individuals participating in a phase 3 clinical trial. Activated follicular helper T (Tfh), non-Tfh and memory CD4+ T cells were detected in almost all subjects early after the first vaccine dose. Act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
0
14
1
1
Order By: Relevance
“…Regarding immunity, a two-dose regimen of SV can produce B cell and CD4 T cell activation in addition to eliciting the production of notable levels of anti-RBD antibodies able to neutralize the SARS-CoV-2 variants of concern. After SV administration, helper T lymphocyte numbers are augmented, Th2 profiles are prevalent, and increased Treg cells are also found. Three months after the second SV dose, the number of central and effector memory CD4 + and CD8 + T cells as well as serum antibody levels decreased significantly. , However, remarkable amounts of IFN-γ- and granzyme B-producing cells are detected at 28 and 90 days postvaccination …”
Section: Discussionmentioning
confidence: 99%
“…Regarding immunity, a two-dose regimen of SV can produce B cell and CD4 T cell activation in addition to eliciting the production of notable levels of anti-RBD antibodies able to neutralize the SARS-CoV-2 variants of concern. After SV administration, helper T lymphocyte numbers are augmented, Th2 profiles are prevalent, and increased Treg cells are also found. Three months after the second SV dose, the number of central and effector memory CD4 + and CD8 + T cells as well as serum antibody levels decreased significantly. , However, remarkable amounts of IFN-γ- and granzyme B-producing cells are detected at 28 and 90 days postvaccination …”
Section: Discussionmentioning
confidence: 99%
“…For instance, in 41 subjects from the Wuhan region with COVID-19, Huang et al [ 19 ] observed that infected patients presented high plasma levels of IL-1β, IFNɣ, and MCP-1, which likely leads to the activation of a Th1 cell profile. In addition, recent studies analyzing the immune response after vaccination observed that, in vaccinated patients, the response to infection is characterized by a Th1 profile that is associated with a better outcome in infected patients [ 20 ]. However, our findings highlighted that patients admitted to the ICU had a higher secretion of Th2-related cytokines (e.g., IL-4, IL-5, and IL-6).…”
Section: Discussionmentioning
confidence: 99%
“…Both induced mainly systemic immunity as they were administered intramuscularly (IM) [ 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ]. Humoral and cellular immunity developed by the individuals that were immunized with S1 protein-based vaccines was directed against this antigen [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ], whereas those that were inactivated virus-based, induced responses against the different viral antigens [ 116 , 117 , 118 ], including the S1 protein [ 117 , 118 , 119 , 120 , 121 , 122 , 123 ]. These same vaccines were modified for intranasal use and are under preclinical and clinical studies to establish if they can induce effective mucosal immunity [ 124 , 125 , 126 , 127 , 128 ].…”
Section: Immune Response Against Sars-cov-2 Induced By Vaccinationmentioning
confidence: 99%
“…(b) SARS-CoV-2 vaccine application: less than a year after the pandemic, several vaccines became available and started to be used massively. Some are based on the S1 protein, which is carried by other viral vectors (ChAdOx1, Ad3 and Ad5, AZD1222, SPUTNIK V, Ad5-nCoV) [ 114 , 115 ]; others are based on mRNA that codifies for the S1 protein (BNT162b2, mRNA1273) [ 116 , 117 , 118 ]. Others use the inactivated whole virus [ 119 , 120 , 121 ] or the isolated S1 protein [ 122 , 123 , 124 ], or virus-like particles [ 144 , 145 , 146 , 147 , 148 , 149 ].…”
Section: Advance In Obtaining Herd Immunity Against Sars-cov-2mentioning
confidence: 99%